СПОЛЬЗОВАНИЕ ГРУППОВЫХ ТЕХНОЛОГИЙ В ОБУЧЕНИИ ИНОСТРАННЫМ ЯЗЫКАМ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the importance of using group technologies in teaching foreign languages, the types and prospects of these technologies.
Keywords: learning process, group technologies, group discussions and projects.